2015
DOI: 10.1515/mms-2015-0036
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis Of Accuracy Of Selected Methods Of Measuring The Thermal Resistance Of IGBTs

Abstract: In the paper selected methods of measuring the thermal resistance of an IGBT (Insulated Gate Bipolar Transistor) are presented and the accuracy of these methods is analysed. The analysis of the measurement error is performed and operating conditions of the considered device, at which each measurement method assures the least measuring error, are pointed out. Theoretical considerations are illustrated with some results of measurements and calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…Considering the error of measurements of the thermal parameters of semiconductor devices, presented − among others − in the papers [12,21] it can be observed that for the measurements of thermal resistance with the employed method, with the applied instruments and in the given conditions of the power supply of the examined diode, it does not exceed 5%. …”
Section: Measurement Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering the error of measurements of the thermal parameters of semiconductor devices, presented − among others − in the papers [12,21] it can be observed that for the measurements of thermal resistance with the employed method, with the applied instruments and in the given conditions of the power supply of the examined diode, it does not exceed 5%. …”
Section: Measurement Resultsmentioning
confidence: 96%
“…The ability of removing heat generated in an electronic device can be characterized − among others − by the thermal resistance Rth or the transient thermal impedance Zth(t) [11,12]. The values of these parameters depend on the construction of cooling system of the device [8,13,14], the device case being its essential component [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In this range, we observe an electrothermal breakdown Górecki, 2009, 2010); it means that the dynamic output resistance of the transistor changes its sign from positive to negative. The differences observed in Figure 4 between the results of calculations and measurements probably are a result of the known dependence of the device thermal resistance on the dissipated power (Górecki and Górecki, 2015). This dependence is omitted in the considered model to obtain convergence of calculations.…”
Section: Investigations Resultsmentioning
confidence: 97%
“…where, t OX ϭ thickness of the layer SiO 2 ; C GCO ϭ gate-drain capacitance for the unit of the channel length; In turn, the thermal model contains the controlled current source G th representing the power dissipated in the transistor, the voltage source T a representing the ambient temperature and the RC network modelling transient thermal impedance of the investigated transistor (Górecki and Górecki, 2015).…”
Section: Model Formmentioning
confidence: 99%
“…The accuracy of indirect electrical methods of measuring thermal parameters of the IGBT is analysed in [27,34]. Based on the considerations presented in the cited papers, the following analytical formula describing the relative error of measurements of thermal resistance R thT can be obtained.…”
Section: Measurement Methodsmentioning
confidence: 99%